Novel View Synthesis interactions from a user perspective - Eklund,Gustaf; Magnusson,Hugo (2025)
This master’s thesis was performed at Axis Communications with the goal of exploring the use of Novel View Synthesis (NVS) - in particular, NeRF and Gaussian Splatting - in camera surveillance. This was done by iteratively creating prototypes and performing user testing on these according to the iterative design process. The prototypes were to be developed with existing implementations of NVS techniques. Over the course of the thesis, three iterations of a prototype were developed, with the last two being user tested. The study found that there is a place for commercial use of NVS in camera surveillance, although the current state of the technology is not yet in a usable state for our defined use case, mainly for performance reasons. The conclusion was made that when using NVS certain interactions need to be taken into account, such as the novelty of the technology, and how the cognitive models of users differ from the real model presented through new technology.
Keywords: User centered design; Novel View Synthesis; Machine learning; Neural Radiance Fields (NeRF); Gaussian Splatting; Camera surveillance; Video Management System